Islamic Religious Education as A Core Curriculum of National Education in Schools - Nugraha, Mulyawan Safwandy; Bakhtiar, Yusup Hamdani; Nasir, Tatang Muh (Indonesian Journal on Education (IJoEd), 2024)
Islamic Religious Education not only takes the discourse on religious knowledge course material to students but also guides students to behave according to the values taught by religion that promote karakul karma or noble character as the primary behavior the learner should own. The position of Isla, mic religious education, among other subjects at school, is the core of the national education curriculum. Therefore, practice in the field should be about providing transparency, understanding, and application process, thus giving birth to inclusive attitudes and behaviors equivalent to other subjects or even prioritized. It puts the subjects of Islamic religious education as a core subject in the school curriculum, which is a need and a necessity. This is an intelligent effort to strengthen forms of Islamic religious education in the school curriculum. So, Islamic religious education covers all aspects of integrated subjects in knowledge, attitudes, behavior, and social interaction.